The regulated secretory pathway in neuroendocrine cells - Rafael Vazquez-Martinez (Frontiers Research Topics, 2014)
The regulated secretory pathway is a hallmark of neuroendocrine cells. This process comprises many sequential steps, which include ER-associated protein synthesis, post-translational modification of proteins in the Golgi complex, sorting and packing of secretory proteins into carrier granules, cytoskeleton-based granule transport towards the plasma membrane and tethering, docking and fusion of granules with specialized releasing zones. Each stage is subjected to a rigorous regulation by a plethora of factors that function in a spatially and temporarily coordinated fashion. Much effort has been devoted to characterize the precise role of the regulatory proteins participating in the different steps of this process and to identify new factors in order to obtain a unifying picture of the secretory pathway. In spite of this and given the enormous complexity of the process, certain stages are not fully understood yet and many players remain to be identified. The aim of this Research Topic is to gather review articles and original research papers on the molecular mechanisms that govern and ensure the correct release of neuropeptides.